Genome-Wide Analysis of MicroRNA Responses to the Phytohormone Abscisic Acid in Populus euphratica - Duan, Hui; Lu, Xin; Lian, Conglong; An, Yi; Xia, Xinli; Yin, Weilun (Frontiers in Plant Science, 2016)
MicroRNA (miRNA) is a type of noncoding small RNA with a regulatory function at the posttranscriptional level in plant growth development and in response to abiotic stress. Previous studies have not reported on miRNAs responses to the phytohormone abscisic acid (ABA) at a genome-wide level in Populus euphratica, a model tree for studying abiotic stress responses in woody plants. Here we analyzed the miRNA response to ABA at a genome-wide level in P. euphratica utilizing high-throughput sequencing. To systematically perform a genome-wide analysis of ABA-responsive miRNAs in P. euphratica, nine sRNA libraries derived from three groups (control, treated with ABA for 1 day and treated with ABA for 4 days) were constructed. Each group included three libraries from three individual plantlets as biological replicate. In total, 151 unique mature sequences belonging to 75 conserved miRNA families were identified, and 94 unique sequences were determined to be novel miRNAs, including 56 miRNAs with miRNA* sequences. In all, 31 conserved miRNAs and 31 novel miRNAs response to ABA significantly differed among the groups. In addition, 4132 target genes were predicted for the conserved and novel miRNAs. Confirmed by real-time qPCR, expression changes of miRNAs were inversely correlated with the expression profiles of their putative targets. The Populus special or novel miRNA-target interactions were predicted might be involved in some biological process related stress tolerance. Our analysis provides a comprehensive view of how P. euphratica miRNA respond to ABA, and moreover, different temporal dynamics were observed in different ABA-treated libraries.